Poetry, punctuation and performance: Was there an aural context for Dudo of Saint-Quentin’s Historia Normannorum? - Benjamin Pohl (Tabularia)
This article explores the possibility of an aural and/or performative context for the reception and dissemination of Dudo of Saint-Quentin’s Historia Normannorum. Scholarship to date has produced two main schools of thought concerning the Historia Normannorum’s target audiences during the eleventh and twelfth centuries, one of which discusses Dudo’s work in the capacity of a Latin school book, thereby emphasising its didactic and educational purpose, whereas the other identifies the main circles of reception at the courts of the Norman dukes and their peers, thus stressing the text’s potential for dynastic self-fashioning, ritual and display. Drawing on the primary evidence of the surviving eleventh- and twelfth-century manuscripts, and combining it with recent theoretical work concerning the different modes of literary communication, this article argues that these schools of thoughts are not mutually exclusive. Based on a detailed study of the manuscripts’ punctuation and mise-en-page (including their use of colour), the article showcases the Historia Normannorum as a “multimedia text” that rather naturally lent itself to being read and/or performed in an aural setting. Conceptualising Norman literature and historiography in such a way significantly enriches and transforms our understanding of literary and poetic culture in the Norman and Anglo-Norman worlds.